1976
DOI: 10.1107/s0567740876009588
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of CuTe2Cl

Abstract: CuTe2C1 is monoclinic, space group P21/c, with a=8.207, b=4.935, c= 15.279 A, fl= 134-92 °, Z=4.722 independent intensities were measured and the structure was refined to R = 5.6 %. The basic structure unit is a pseudo-fourfold screw of Te atoms along b. The Te-Te distances in the screw are 2-737 and 2.792 A. Cu-C1-Cu links connect the screws to layers in the ab plane. The coordination of the Cu atom by Te and C1 is fourfold with the geometry of a slightly distorted tetrahedron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
1
9
0
2
Order By: Relevance
“…Interestingly, we found that the area of the parallelogram at the base of (a, c) in this work almost coincides with that at the base of (b, c) in Material Project. The results obtained here are very close to those determined in the previous experimental study (a ¼ 8.21, b ¼ 4.94, and c ¼ 15.28 Å for the lattice constants and θ 1 ¼ 90 , θ 2 ¼ 90 , θ 3 ¼ 135 for the angles), [23] which attests the reliability of our simulations. Figure 1b shows the atomic structure of the CuTe 2 Cl monolayer.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we found that the area of the parallelogram at the base of (a, c) in this work almost coincides with that at the base of (b, c) in Material Project. The results obtained here are very close to those determined in the previous experimental study (a ¼ 8.21, b ¼ 4.94, and c ¼ 15.28 Å for the lattice constants and θ 1 ¼ 90 , θ 2 ¼ 90 , θ 3 ¼ 135 for the angles), [23] which attests the reliability of our simulations. Figure 1b shows the atomic structure of the CuTe 2 Cl monolayer.…”
supporting
confidence: 91%
“…Via the reaction of stoichiometric amounts of CuCl and Te at 350 °C, the bulk CuTe 2 Cl structure has been synthesized by Fenner . On the one hand, we found that CuTe 2 Cl belongs to the family of the Cu–VII–VI compound, which is a monoclinic structure with the space group of P2 1 /c.…”
mentioning
confidence: 99%
“…A series of nine compounds was prepared by hydrothermal methods from the corresponding mineral acids [3]. Tellurium and the copper(I) halides form two isostructural series of com-pounds with the compositions CuXTe [4±6] and CuXTe 2 [7,8] (X = Cl, Br, I), respectively. They all contain formally neutral infinite one-dimensional (1 D) tellurium chains 1 ∞ [Te].…”
Section: Introductionmentioning
confidence: 99%
“…The Se-Se bonds in 1 range between 2.3225(4) and 2.4321(4) Å, the respective Te-Te bond lengths in 2 between 2.7070(6) and 2.8444 (6) can be regarded as stacked five-membered CuSe 4 rings alternating rotated by 180°. The conformation of these rings is for example similar to the CuTe 5 rings in CuTeI [6] and CuTe 2 Cl [7].…”
mentioning
confidence: 91%